Drug-eluting stent coatings. (February 2012) - Ma, Xiaodong; Wu, Tim; Robich, Michael P
Over the past decade, drug-eluting stents (DES) have greatly transformed the field of interventional cardiology. Generally, three components are included in a DES system: a metal stent platform, a drug carrier or so called 'stent coating'' and a drug. As such, stent coating plays an important role in the performance of DES. This article will review the evolution of stent coatings and their role in the development of restenosis and thrombosis.